Strategi Pengembangan Usaha Industri Gula Merah Tebu di Kabupaten Tulungagung Provinsi Jawa Timur - ACHMAD RIFA’I; I MADE SUDARMA; WIDHIANTHINI WIDHIANTHINI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
The Brown Cane Sugar Industry Business Development Strategy in TulungagungEast Java Province The brown cane sugar industry in Tulungagung is a home industry that is owned byindividuals and has many obstacles to run. This research aims to analyze the businessfeasibility based on the income and BEP (Break Even Point) and to formulate a businessdevelopment strategy for the sugar cane brown sugar business. This study uses dataanalysis methods in the form of qualitative descriptive, quantitative analysis for the level ofbusiness feasibility, and SWOT analysis (Strengths, Weaknesses, Opportunities, Threats).The brown cane sugar industry in the past year has been producing for 238 days/year whichrequires 15 tons/day of raw sugar cane materials. The revenue obtained from pattern I wasIDR 4.027.873/day of production, pattern II was IDR 3.252.623/day of production, andpattern III was IDR 3.351.373/day of production. The BEP calculation in pattern I was IDR 2.617.072/day of production or 292,5 kg, BEP pattern II was IDR 2.698.287/productionday or 307 kg, and BEP pattern III was IDR 2.779.504/production day or 321 kg. TheSWOT analysis was conducted using analysis of internal and external factors that producesseveral strategies. Several alternative strategies produced are increasing the productionvolumes, expanding the marketing reach, forming joint business groups, determining theproduct distribution schedules, using the appropriate technology, utilizing informationtechnology to promote the products, and managing the business licensing.